Impact of enzymatic hydrolysis on the nutrients, phytochemicals and sensory properties of oil hemp seed cake (Cannabis sativa L. FINOLA variety). (1st August 2020) - Pap, Nora; Hamberg, Leena; Pihlava, Juha-Matti; Hellström, Jarkko; Mattila, Pirjo; Eurola, Merja; Pihlanto, Anne
Highlights: Defatting with SC-CO2 lightens the color of oil hemp seed cake. The sediments after enzymatic processing are rich in proteins and phytochemicals such as protanthocyanidins an lignanamides. Most of the phytic acid is remained in the sediments after hydrolyses. Hydrolysis sediments are promising ingredients for model foods. Abstract: Enzymatic hydrolysis of the oil hemp seed (FINOLA variety) cake and defatted hemp seed cake by SC-CO2 was carried out using Flavorpro 750 MDP and Promod 439 L enzymes, and proximate composition, proanthocyanidins, phytic acid, lignanamides and cannabinoids were determined from the separated phases. CIELAB* color parameters were measured, while trained panelists evaluated taste, color, and smell in 1–9 Hedonic scale. Ten lignanamides, seven cannabisin-type and three grossamide-type, were found, from the cannabinoids, only cannabidiolic acid was detected. Protein, fat, ash, lignanamides and proanthocyanidins remained mostly in the sediments after the hydrolysis process in the Flavorpro treated samples, while dry matter, fat and ash was released mostly to liquids in Promod treated samples. The defatting process by SC-CO2 resulted in a higher lightness and the enzymatic processing did not have effect on the color attributes. Sediments from the enzymatic treatment were tastier, with better color and smell than liquids.